Myeloid-derived suppressor cell: A crucial player in autoimmune diseases - Xu, Dandan; Li, Cheng; Xu, Yushan; Huang, Mingyue; Cui, Dawei; Xie, Jue (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are identified as a highly heterogeneous group of immature cells derived from bone marrow and play critical immunosuppressive functions in autoimmune diseases. Accumulating evidence indicates that the pathophysiology of autoimmune diseases was closely related to genetic mutations and epigenetic modifications, with the latter more common. Epigenetic modifications, which involve DNA methylation, covalent histone modification, and non-coding RNA-mediated regulation, refer to inheritable and potentially reversible changes in DNA and chromatin that regulate gene expression without altering the DNA sequence. Recently, numerous reports have shown that epigenetic modifications in MDSCs play important roles in the differentiation and development of MDSCs and their suppressive functions. The molecular mechanisms of differentiation and development of MDSCs and their regulatory roles in the initiation and progression of autoimmune diseases have been extensively studied, but the exact function of MDSCs remains controversial. Therefore, the biological and epigenetic regulation of MDSCs in autoimmune diseases still needs to be further characterized. This review provides a detailed summary of the current research on the regulatory roles of DNA methylation, histone modifications, and non-coding RNAs in the development and immunosuppressive activity of MDSCs, and further summarizes the distinct role of MDSCs in the pathogenesis of autoimmune diseases, in order to provide help for the diagnosis and treatment of diseases from the perspective of epigenetic regulation of MDSCs.